2021
DOI: 10.1088/1755-1315/918/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Faloak (Sterculia quadrifida R.Br.) bark harvesting for curing hepatitis in Kupang City: Herbal medicine in the urban environment

Abstract: Trees in an urban environment play an important role. Studies have shown that the presence of trees can improve human physical and mental health. People in Kupang, Nusa Tenggara Timur Province, Indonesia, harvest Sterculia quadrifida R.Br. (faloak) bark for medicinal decoction for hepatitis and energy booster. Hepatitis cases in Kupang City continue to increase, from 40 cases in 2016 to 147 cases in 2017 and 220 cases in 2018. This study aimed to assess S. quadrifida bark harvesting intensity and its utilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Sterculia quadrifida is widely used in traditional medicine. For example, Siswadi et al, 21 reported that the bark of S. quadrifida was used to treat hepatitis. In addition, several studies have shown that the bark of S. quadrifida has cytotoxic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Sterculia quadrifida is widely used in traditional medicine. For example, Siswadi et al, 21 reported that the bark of S. quadrifida was used to treat hepatitis. In addition, several studies have shown that the bark of S. quadrifida has cytotoxic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Faloak is traditionally boiled, brewed, and consumed to cure various diseases, as believed (Lalong et al, 2022). For generations, Kupang society has used Faloak plants to cure hepatitis (Siswadi et al, 2016). Furthermore, this plant is used to cure dengue, wound treatment, eye pain, insect bites, hepatitis, typhus, and stamina enhancement (Uslan et al, 2020;Riwu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…3) The utilization of the Faloak plants as the learning material in the module is scarce. Based on the literature review conducted in several reputable journals, research regarding Faloak plants in Kupang is restricted to Faloak plants as the curing disease (Dean et al, 2019;Siswadi et al, 2021) and the anatomy and morphological aspects of the plants (Asmiati et al, 2019;Uslan et al, 2020;Jannah et al, 2022). Therefore, integrating the Faloak plant as the learning material is new and has become the originality of the current research.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies have shown that S. quadrifida seeds contain potent cytotoxic compounds, which have the potential to inhibit the growth of cancer cells. For example, a study conducted by Rukayadi et al 7 identified a novel cytotoxic compound, namely 3,3',5,5'-tetramethoxybiphenyl-2,2'-diol, from the methanol extract of S. quadrifida seeds. The compound exhibited cytotoxic activity against various cancer cell lines, including human breast adenocarcinoma (MCF-7), human colon adenocarcinoma (HT-29), and human lung adenocarcinoma (A549) cells.…”
Section: Introductionmentioning
confidence: 99%